Climate Change and Human Health: Time to Recognize the New Threat - Y. J. Anupama (APIK Journal of Internal Medicine)
Climate change (CC) is an important, emerging global threat to human health. The temperature on the surface of the earth has been increasing rapidly over the last few decades. Global warming (GW) has cascading effects on the environment affecting rainfall, precipitation, and sea water levels. Much of the GW is due to human activity and is linked to large scale industrialization, urbanization, and combustion of fossil fuels. The essential requisites for life namely, clean air, clean water, and good quality food are getting depleted rapidly. The increasing air and water pollution influences food quality and quantity. These changes compromise many aspects of human health resulting in malnutrition, infections, and rising burden of cardiometabolic diseases. There are also many socioeconomic consequences due to CC and extreme weather events which have an impact on food security and mental health. Efforts to combat the health impact of CC involve the measures to control CC primarily. Global, loco-regional and individual efforts at adaptation and mitigation must be carried out on a war-footing to prevent the surge in diseases.